MANAJEMEN KELASINKLUSIF: STRATEGIS PENDISIPLINAN DAN PEMBENTUKAN KARAKTER ANAK PEKERJA MIGRAN PPWNI KLANG, MALAYSIA - Anastasia Fidelyna B.Openg; Rinaldi Yusup (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The International Internship Program serves as a practical learning experience for final-year students from Nusa Putra University, Sukabumi. This study aims to apply pedagogical competencies, child psychology principles, and classroom management techniques within a non-formal educational setting: the Indonesian Citizen Learning Center (PPWNI) in Klang, Selangor, Malaysia. This institution offers alternative educational opportunities for the children of Indonesian Migrant Workers (PMI) who face challenges regarding administrative documentation (undocumented status). The study employs a qualitative descriptive approach based on hands-on teaching practice across grades 1 through 6. Instruction focuses primarily on strengthening literacy and numeracy skills while fostering adaptive character traits. Data collection involved participant observation, in-depth interviews with center administrators, and documentation of daily activities. Findings indicate that managing instruction at the learning center faced significant obstacles, including low student discipline, fluctuating learning motivation, and a lack of adequate educational facilities and infrastructure. To address these issues, classroom management strategies were adapted to incorporate relevant contextual learning approaches and behavior modification methods. These strategies proved effective in enhancing student concentration, active participation, and orderliness, despite the students' diverse socio-cultural backgrounds. Overall, this international internship program not only succeeded in enhancing the professional skills and social competencies of the students as future educators in the global arena but also strengthened Indonesia's educational diplomacy abroad. The program represents a tangible step toward ensuring inclusive access to basic education for migrant children in vulnerable legal situations.